1997
DOI: 10.1037/0735-7036.111.3.286
|View full text |Cite
|
Sign up to set email alerts
|

Gaze following and joint attention in rhesus monkeys (Macaca mulatta).

Abstract: Gaze and attention direction provide important sources of social information for primates. Behavioral studies show that chimpanzees spontaneously follow human gaze direction. By contrast, non-ape species such as macaques fail to follow gaze cues. The authors investigated the reactions of rhesus macaques (Macaca mulatta) to attention cues of conspecifics. Two subjects were presented with videotaped images of a stimulus monkey with its attention directed to 1 of 2 identical objects. Analysis of eye movements rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
172
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 236 publications
(176 citation statements)
references
References 32 publications
3
172
0
1
Order By: Relevance
“…Prior to this, it seems that children actually ignore the orientation of the eyes and simply use the position of the head as an attention-following cue (Corkum & Moore, 1995). By and large, nonhuman primates-the nonape species in particular-also use head orientation as the primary cue to another individual's direction of attention (e.g., Emery, Lorincz, Perrett, Oram, & Baker, 1997;Itakura & Anderson, 1996). Experimental studies with human participants have indicated that head cues are able to trigger rapid and reflexive shifts of a viewer's spatial attention (Langton & Bruce, 1999) and are very difficult to ignore, even when the viewer attempts to respond to directional information presented auditorily (Langton, 2000;.…”
Section: Perception Of Head Orientationmentioning
confidence: 99%
“…Prior to this, it seems that children actually ignore the orientation of the eyes and simply use the position of the head as an attention-following cue (Corkum & Moore, 1995). By and large, nonhuman primates-the nonape species in particular-also use head orientation as the primary cue to another individual's direction of attention (e.g., Emery, Lorincz, Perrett, Oram, & Baker, 1997;Itakura & Anderson, 1996). Experimental studies with human participants have indicated that head cues are able to trigger rapid and reflexive shifts of a viewer's spatial attention (Langton & Bruce, 1999) and are very difficult to ignore, even when the viewer attempts to respond to directional information presented auditorily (Langton, 2000;.…”
Section: Perception Of Head Orientationmentioning
confidence: 99%
“…In a laboratory setting, people respond more quickly to targets that are the object of another's attention, even when this social cuing is brief or consistently misleading (1)(2)(3). Monkeys' attention also follows the gaze of others (4), and the similar magnitude and time course of gaze following by rhesus macaques and humans (5) implicates shared neural mechanisms. The ability to follow gaze is believed to be an important foundation for theory of mind (6,7); thus, the neural processes governing gaze following are relevant both to the evolution of social cognition (8)(9)(10) and to clinical disorders, such as autism, associated with social attention deficits (11)(12)(13)(14).…”
mentioning
confidence: 93%
“…Humans, however, are not unique in their sensitivity to gaze. Gaze following (co-orienting gaze with a conspecific or human experimenter) has been reported in apes (e.g., Bräuer, Call, & Tomasello, 2005), monkeys (e.g., Emery, Lorincz, Perrett, Oram, & Baker, 1997), ungulates (e.g., Kaminski, Riedel, Call, & Tomasello, 2005), dogs (e.g., Bräuer, Call, & Tomasello, 2004), birds (e.g., ravens (Corvus corax), Bugnyar, Stowe, & Heinrich, 2004), and reptiles (red-footed tortoise (Geochelone carbonaria), Wilkinson, Mandl, Bugnyar, & Huber, 2010). Moreover, gaze aversion, in which animals respond fearfully to direct gaze, presumably because forward facing eyes are associated with predator attacks, has been reported in a similar breath of taxa including mammals (e.g., Coss, 1978b), birds (e.g., Carter, Lyons, Cole, & Goldsmith, 2008;von Bayern & Emery, 2009), reptiles (basking black iguana (Ctenosaura similis), Burger, Gochefeld, & Murray Jr, 1991), and fish (African jewel fish (Hemichromis bimaculatus), Coss, 1979) (see Davidson, Butler, Fernández-Juricic, Thornton, & Clayton, 2013, for review).…”
Section: Introductionmentioning
confidence: 99%